Evolutionary rates of body-size-related genes and ecological factors involved in driving body size evolution of squamates - Wu, Haixia; Gao, Shuo; Xia, Longjie; Li, Peng (Frontiers in Ecology and Evolution, 2022)
Body size is one of the most important traits of an organism. Among reptiles, both lizards and snakes show body size differences that span a similar six orders of magnitude variation. However, the molecular mechanisms underlying body size variation in squamates remains obscure. Here, we performed comparative genomic analyses of 101 body-size-related genes from 28 reptilian genomes. Phylogenetic analysis by maximum likelihood (PAML) revealed that snakes showed higher evolutionary rates in body-size-related genes, and had an almost two-fold increase in the number of positively selected genes ( 20.3%) compared with lizards ( 8.9%). The high similarities in dN/dS values were obtained between the branches of large-bodied lizards and large-bodied snakes by Spearman correlation analysis. Combining the results from site model, branch-site model and clade model analyses, we found some key genes regulating the evolution of body size in squamates, such as COL10A1, GHR, NPC1, GALNS, CDKN2C, FBN1, and LCORL. Phylogenetic generalized least squares (PGLS) indicated that AKT1, BMP1, IGF1, SOX5, SOX7 in lizards and BMP5, BMP7, GPC6, SH2B3, SOX17 in snakes were significantly correlated with body length and body mass. Furthermore, ecological factors have varying degrees of impact on body size and the evolutionary rate of body-size-related genes in squamates. Intriguingly, climate had little effect on body size of lizards and snakes, but the contribution of climate-related factors to the variation in evolutionary rate of body-size-related genes were relatively higher. Our study lays a foundation for a comprehensive understanding of genetic mechanisms of body size evolution in squamates during the process of adapting to terrestrial life.